PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Maria Qibti Mahdiana; Muhammad Nuryatno Amin (Jurnal Akuntansi Trisakti, 2020)
This study investigated the effect of profitability, leverage, company size, and sales growth on tax avoidance. This research uses quantitative method, the data used are secondary data taken from financial reports and company sustainability reports. The sampling technique used a purposive sampling method of 25 companies listed on the Indonesia Stock Exchange from 2015 to 2018. The total sample used were 100 companies that revealed complete financial and sustainability reports from 2015 to 2018. Data analysis techniques used descriptive statistical tests and multiple regression tests. The result show that (1) profitability has a significant positive effect on tax avoidance (2) leverage has a significant positive effect on tax avoidance (3) company size does not affect tax avoidance and (4) sales growth does not affect the tax avoidance variable.